TRIAXIAL UNLOADING TEST OF ROCKS AND ITS IMPLICATION FOR ROCK BURST - Huang R.Q.; Wang X.N.; Chan L.S. (My University, 2001)
The behaviour of rock deformation and its failure characteristics under loading and unloading conditions are substantially different. In this paper, triaxial unloading tests have been designed to simulate the unloading process during tunnel excavation in three kinds of rock (granite, migmatitic granite and limestone). The results show that elastic moduli obtained under unloading conditions are generally less than under loading conditions. The strength of the rock samples also decreases with an increasing rate of unloading. This study reveals that rock bursts during tunnelling in a high in-situ stress area could be controlled or reduced by lowering the excavation speed or applying precautionary measures to control the displacement of surrounding rocks.
Keywords: TRIAXIAL TEST; UNLOADING; ROCK BURST; GRANITE